Parental Relationship in Child Raising Psychological Properties - Alimova Nargiza Usmanovna (Genius Publishing Group, 2022)
This article is about the role of parents and the social environment in the upbringing of children, as well as the formation of positive qualities in the process of upbringing
Keywords: Formation of the child; parents; education; family environment